2008
DOI: 10.14778/1453856.1453882
|View full text |Cite
|
Sign up to set email alerts
|

Parallelizing query optimization

Abstract: Many commercial RDBMSs employ cost-based query optimization exploiting dynamic programming (DP) to efficiently generate the optimal query execution plan. However, optimization time increases rapidly for queries joining more than 10 tables. Randomized or heuristic search algorithms reduce query optimization time for large join queries by considering fewer plans, sacrificing plan optimality. Though commercial systems executing query plans in parallel have existed for over a decade, the optimization of such plans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 31 publications
0
47
0
Order By: Relevance
“…Although in DBMSs several optimization approaches exist, which would benefit from the high parallelism of GPUs, so far, the application of GPUs in DBMSs is limited to selectivity estimation. As Han et al showed, other optimization approaches, such as DP for join-order optimization, also benefit from parallelization [17]. Hence, we expect that the higher parallelism of GPUs would also increase the quality of these optimization approaches in DBMSs.…”
Section: Dijkstra Algorithmmentioning
confidence: 95%
See 3 more Smart Citations
“…Although in DBMSs several optimization approaches exist, which would benefit from the high parallelism of GPUs, so far, the application of GPUs in DBMSs is limited to selectivity estimation. As Han et al showed, other optimization approaches, such as DP for join-order optimization, also benefit from parallelization [17]. Hence, we expect that the higher parallelism of GPUs would also increase the quality of these optimization approaches in DBMSs.…”
Section: Dijkstra Algorithmmentioning
confidence: 95%
“…Nevertheless, the increased parallelism of the DP approach for join-order optimization can be used on multi-core CPUs to provide a linear speedup [17]. This speed up improves the applicability of the DP approach for join-order optimization from 12 joined relations to 22-25 joined relations [17].…”
Section: Dynamic Programmingmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to exploit multicore architectures to their fullest, we may have to devise new index structures or reimplement database operations accordingly. In fact, researches along this line are already producing highly promising (and even surprising) results in the database community [17,[11][12][13]29,6]. Certainly we do not want to find ourselves struggling to squeeze performance out of just a single core while all other 31 cores remain idle!…”
Section: Introductionmentioning
confidence: 99%